2011
DOI: 10.19030/jabr.v23i3.1390
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis Of The Comparative Predictive Abilities Of Operating Cash Flows, Earnings, And Sales

Abstract: <p class="MsoBodyText" style="text-align: justify; margin: 0in 34.2pt 0pt 0.5in;"><span style="color: black; font-size: 10pt;"><span style="font-family: Times New Roman;">Prior studies (e.g., Greenburg et al., 1986; Murdoch and Krause, 1989) provide evidence that earnings outperforms historical cash flows in predicting future cash flows. Later research (e.g., Barth et al., 2001) demonstrates that the major accrual components of earnings each possess significant explanatory power in predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
10
0
2
Order By: Relevance
“…Many studies concluded that working capital from operations and net income before extraordinary items and discontinued operations plus depreciation and amortization are powerful than other cash flow measures (Arnold, Clubb, Manson & Wearing, 1991;Quirin, O'Bryan, Wilcox & Berry,1999;Quirin, O'Bryan & Berry,2000) Study by Jordan, Waldron, and Clark (2007) in USA compared ability of cash flow from operations, earnings and sales in predicting future cash flow of 100 companies of the Fortune 1000 companies and finds that sales are a better predictor of future cash flow than cash flow from operations and earnings.…”
Section: Empirical Evidence From Prediction Of Future Cash Flows Whermentioning
confidence: 99%
“…Many studies concluded that working capital from operations and net income before extraordinary items and discontinued operations plus depreciation and amortization are powerful than other cash flow measures (Arnold, Clubb, Manson & Wearing, 1991;Quirin, O'Bryan, Wilcox & Berry,1999;Quirin, O'Bryan & Berry,2000) Study by Jordan, Waldron, and Clark (2007) in USA compared ability of cash flow from operations, earnings and sales in predicting future cash flow of 100 companies of the Fortune 1000 companies and finds that sales are a better predictor of future cash flow than cash flow from operations and earnings.…”
Section: Empirical Evidence From Prediction Of Future Cash Flows Whermentioning
confidence: 99%
“…One major decision in the research involves whether to investigate these relationships using a direct or indirect approach. The indirect method uses share prices to proxy for future cash flows (Ball and Brown, 1968;Rayburn, 1986;Wilson, 1986Wilson, , 1987Bowen et al, 1987;Ali, 1994;Dechow, 1994;Cheng et al, 1996;Pfieffer et al, 1998;Jordan et al, 2007). Other researchers (Lipe, 1986;Barth et al, 1992;Barth et al, 1999;Barth et al, 2001) note weaknesses in the share price proxy approach for predicting future cash flows and consequently use the direct approach.…”
Section: Literature Review and Research Questionmentioning
confidence: 99%
“…Finally, we include the percentage change in sales in our set of regressors. This inclusion is motivated by the findings of Jordan, Waldron, and Clark (2007) who show that sales predict stock prices and Barbee, Mukherji, and Raines (1996) who found that sales yield is one of the strongest determinants of returns.…”
mentioning
confidence: 99%